Hello Conal,

GHC implementation of functional dependencies is incomplete: it will use functional dependencies during type inference (i.e., to determine the values of free type variables), but it will not use them in proofs, which is what is needed in examples like the one you posted.  The reason some proving is needed is that the compiler needs to figure out that for each instantiation of the type `ta` and `tb` will be the same (which, of course, follows directly from the FD on the class).

As far as I understand, the reason that GHC does not construct such proofs is that it can't express them in its internal proof language (System FC).  It seems to me that it should be fairly straight-forward to extend FC to support this sort of proof, but I have not been able to convince folks that this is the case.  I could elaborate, if there's interest.

In the mean time, the way forward would probably be to express the dependency using type families, which I find tends to be more verbose but, at present, is better supported in GHC.

Cheers,
-Iavor
PS: cc-ing the GHC users' list, as there was some talk of closing the ghc-bugs list, but I am not sure if the transition happened yet.





On Tue, Dec 25, 2012 at 6:15 PM, Conal Elliott <conal@conal.net> wrote:
I ran into a simple falure with functional dependencies (in GHC 7.4.1):

> class Foo a ta | a -> ta
>
> foo :: (Foo a ta, Foo a tb, Eq ta) => ta -> tb -> Bool
> foo = (==)

I expected that the `a -> ta` functional dependency would suffice to prove that `ta ~ tb`, but

    Pixie/Bug1.hs:9:7:
        Could not deduce (ta ~ tb)
        from the context (Foo a ta, Foo a tb, Eq ta)
          bound by the type signature for
                     foo :: (Foo a ta, Foo a tb, Eq ta) => ta -> tb -> Bool
          at Pixie/Bug1.hs:9:1-10
          `ta' is a rigid type variable bound by
               the type signature for
                 foo :: (Foo a ta, Foo a tb, Eq ta) => ta -> tb -> Bool
               at Pixie/Bug1.hs:9:1
          `tb' is a rigid type variable bound by
               the type signature for
                 foo :: (Foo a ta, Foo a tb, Eq ta) => ta -> tb -> Bool
               at Pixie/Bug1.hs:9:1
        Expected type: ta -> tb -> Bool
          Actual type: ta -> ta -> Bool
        In the expression: (==)
        In an equation for `foo': foo = (==)
    Failed, modules loaded: none.

Any insights about what's going wrong here?

-- Conal

_______________________________________________
Glasgow-haskell-bugs mailing list
Glasgow-haskell-bugs@haskell.org
http://www.haskell.org/mailman/listinfo/glasgow-haskell-bugs